Activated autologous blood therapy in recurrent spontaneous abortion: results of a pilot study - Pfeiffer, Kerstin Antje; Sillem, Martin; Daniel, Volker; Kirschfink, Michael; Süsal, Caner; Runnebaum, Benno; Gerhard, Ingrid (Human reproduction, 1998)
This study was undertaken to investigate the influence of activated autologous blood therapy on immunological parameters and on the clinical outcome in patients with recurrent spontaneous abortion. In a prospective trial, 36 women with recurrent spontaneous abortion were treated with intramuscular reinjections of extracorporally haemolysed and ultraviolet irradiated autologous blood. A comprehensive immunological investigation revealed significant changes in lymphocyte subpopulations, plasma complement levels, mitogen stimulation and immunoglobulin levels during the treatment period. No side-effects were reported by the patients. From June 1994 to November 1995, 22 intrauterine and one extrauterine pregnancies occurred, resulting in 19 (86%) live births, two (9%) spontaneous abortions and one (4 %) artificial abortion compared with a 64 % live birth rate in the historical control group. We conclude that activated autologous blood therapy has detectable effects on the immune system, and seems to be promising for further investigation concerning the treatment of idiopathic recurrent spontaneous abortion.